Strengthening Public Relations Practitioners' Capacity to Address Artificial Intelligence Challenges - Wulandari, Maulina Pia; Wachid, Ivan Bimantoro; Argyanti, Talitha; Sasela, Mirel Imelda; Zuhri, Mochamad Fernanda Abuzar; Jukiabtari, Serly Novita; Taqi, Naila (Wikrama Parahita : Jurnal Pengabdian Masyarakat, 2025)
The emergence of digital tools like artificial intelligence (AI) presents unique challenges to public relations practices, making it crucial for practitioners to understand these dynamics and strengthen their competencies for the digital transformation era. A Community Service Team conducted a "Workshop on Enhancing the Capacity of Public Relations Practitioners in Facing the Challenges and Threats of Artificial Intelligence (AI) in Digital Public Relations Practices" in Room 7.2, Building C, FISIP, Universitas Brawijaya, on Tuesday, August 20, 2024. This community service activity falls under problem-based, experiential, and real-world project-based learning methods, specifically Problem-Based Learning, in the form of training/workshops. Its primary objective is enhancing theoretical knowledge and strengthening foundational skills in utilizing AI to formulate effective digital PR strategies. The workshop underscores the critical need for PR professionals to enhance their digital literacy, particularly in AI, to remain competitive in an increasingly digital and data-driven environment.